The Interest in Gateball Sports Between FIK UNM and UKM UMI College Students - Sahabuddin, Sahabuddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to test whether there are differences in the interest of FIK UNM and UMI UKM college students towards the Gateball game. This study was conducted in September 2018. The population in this study was all FIK UNM college students and UMI UKM college students. The sample consisted of 15 FIK UNM college students and 15 UMI UKM college students, the sample in this study was determined using random sampling. Data collection in the study was carried out using questionnaires. The method used for hypothesis testing is the Independent Sample T-test. The results showed that: (1) The results of hypothesis testing obtained a sig value (2-tailed) which is 0.080 greater than 0.05. Thus, it can be concluded that there is no significant difference in interest between FIK UNM college students and UMI UKM towards the Gateball game.